Mechanistic and therapeutic study of novel anti-tumor function of natural compound imperialine for treating non-small cell lung cancer. (30th January 2020) - Lin, Qing; Qu, Mengke; Patra, Hirak K.; He, Shanshan; Wang, Luyao; Hu, Xun; Xiao, Linyu; Fu, Yu; Gong, Tao; He, Qin; Zhang, Ling; Sun, Xun; et al.
Abstract: Ethnopharmacological relevance: Bulbus Fritillaria cirrhosa D. Don (BFC) is a Chinese traditional herbal medicine that has long been used as an indispensable component in herbal prescriptions for bronchopulmonary diseases due to its well-established strong anti-inflammation and pulmonary harmonizing effects. Interestingly, there are few case reports in traditional Chinese medicine available where they found it to contribute in anti-tumor therapies. Imperialine is one of the most favored active substances extracted from BFC and has been widely recognized as an anti-inflammatory agent. Aim of the study: The aim of the current work is to provide first-hand evidences both in vitro and in vivo showing that imperialine exerts anti-cancer effects against non-small cell lung cancer (NSCLC), and to explore the molecular mechanism of this anti-tumor activity. It is also necessary to examine its systemic toxicity, and to investigate how to develop strategies for feasible clinical translation of imperialine. Materials and methods: To investigate anti-NSCLC efficacy of imperialine using both in vitro and in vivo methods where A549 cell line were chosen as in vitro model NSCLC cells and A549 tumor-bearing mouse model was constructed for in vivo study. The detailed underlying anti-cancer mechanism has been systematically explored for the first time through a comprehensive set of molecular biology methods mainly including immunohistochemistry, western blot and enzyme-linked immunosorbent assays. The toxicity profile of imperialine treatments were evaluated using healthy nude mice by examining hemogram and histopathology. An imperialine-loaded liposomal drug delivery system was developed using thin film hydration method to evaluate target specific delivery. Results: The results showed that imperialine could suppress both NSCLC tumor and associated inflammation through an inflammation-cancer feedback loop in which NF-κB activity was dramatically inhibited by imperialine. The NSCLC-targeting liposomal system was successfully developed for targeted drug delivery. The developed platform could favorably enhance imperialine cellular uptake and in vivo accumulation at tumor sites, thus improving overall anti-tumor effect. The toxicity assays revealed imperialine treatments did not significantly disturb blood cell counts in mice or exert any significant damage to the main organs. Conclusions: Imperialine exerts anti-cancer effects against NSCLC both in vitro and in vivo, and this previously unknown function is related to NF-κB centered inflammation-cancer feedback loop. Imperialine mediated anti-cancer activity is not through cytotoxicity and exhibit robust systemic safety. Furthermore, the liposome-based system we commenced would dramatically enhance therapeutic effects of imperialine while exhibiting extremely low side effects both on cellular and in NSCLC model. This work has identified imperialine as a promising novel anti-cancer compound and offered an efficient target-delivery solution that greatly facilitate practical use of imperialine. Graphical abstract: Image 1